Ancestrais que vieram da África: o culto a Egúngún no Candomblé Omo Ilê Agboulá - Rodrigues, Renato (2021)
The present study offers an original contribution to research on the cult of Egúngún and funeral rituals in Candomblé, due to the scarce publications on the subject.Starting from a wide bibliographic survey, a contextualization of the African Diaspora is presented, and, from there, the description of the Terreiro Omo Ilê Agboulá, on the Island of Itaparica.From the cult of Egúngún, the importance of ancestry for Afro-Brazilian religions is revealed and how it is mediated by death.The description of priestly functions, religious spaces and the rituals performed in them allows a better understanding of their social and symbolic dynamics.In this way, we understand that worshiping Egúngún is continuing to fight, preserve, research, and encourage the civilizing values of the African Matrix Religion.Therefore, the African Matrix Religion aims to preserve Planet Earth, respecting and cultivating animal and plant life